STRATEGI KOMUNIKASI INTERPERSONAL DAN PENGELOLAAN KONFLIK UNTUK MENJAGA DINAMIKA KOMUNIKASI DALAM KOMUNITAS K-POP DANCE COVER LIGHT GALAXY ENTERTAINMENT SEMARANG AGAR TETAP EKSIS - Lutfi Oktavia Dewi; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Based on a research, since 2011 K-Pop phenomenon extremely booming not only internationally but also in Indonesia. K-Pop fans then started to imitate the dance of K-Pop idols called dance cover. This research was focused on understanding interpersonal communication strategy and conflict management among K-Pop dance cover community Light Galaxy Entertainment to maintain the dynamic as well as the affirmation of the relationship so that this community is exist and last up until now on. This research used in-depth interview and participant observation method. This research is a qualitative type with case study approach, and used pattern matching analysis method. Data collection done by in-depth interview and participant observation and also other necessary data included. The result of this research show that even when this community is heterogeneous with each member who has diverse background, however the diversity can be overcome by interpersonal approach. there were several conflicts occurred within Light Galaxy Entertainment and complicated self accommodation among the members within heterogeneous community, however it can be solved using interpersonal approach. Besides, by using interpersonal approach the members of this community can manage conflicts and build closer fellowship.